REALITY ORIENTATION MODEL FOR MENTAL DISORDER PATIENTS WHO EXPERIENCE AUDITORY HALLUCINATIONS - Arum Pratiwi; Enita Dewi (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2016)
Introduction: The number of patients with mental illness is increasing every year. The research aim was to develop a model of reality orientation therapy in patients with schizophrenia who had auditory hallucinations. Methods: This design of the study was a sequential exploratory research study which combined qualitative and quantitative approaches. The respondents involved in this study were patients with schizophrenia who experienced auditory hallucinations. Ten respondents who met the criteria were used as the population target in the therapeutic procedure trial. Five nurses who had experience treating patients in a mental hospital were established as experts in the trial instrument development. Initially, the content of the hallucinations were identified using